Estrategias de marketing del Comercial Lubrirepuesto “Alvario” de la parroquia San Juan. - Casa Moran, Jamileth Alexandra (2022)
Lubrirepuesto "Alvario" is a company that is located on Calle 6 de Octubre and Justino Cornejo, belonging to the Parish of San Juan del Cantón San Francisco de Puebloviejo. The deficit of these marketing strategies has affected the image of the commercial in the San Juan parish; due to ignorance of the elements and methods that are part of marketing strategies. Through the development of the case study, it will be possible to know what effect the absence of marketing strategies has on the level of sales and on the image that Lubrirepuesto "Alvario" customers have. The case study is part of the research line: Financial, administrative, tax, audit and control management and its subline is, marketing and commercialization. Therefore, it aims to analyze the factors that affect the lack of marketing strategies, through a SWOT analysis to increase sales; for which the inductive method and descriptive methodology were applied accompanied by bibliographic analysis; To obtain relevant information, the survey was used as a data collection technique, and thus to know the opinion of customers about advertising, customer service, competition, product quality and competitive advantage. With which it was possible to conclude that Lubrirepuesto "Alvario" does not carry out activities related to the development of promotion and advertising tools, lack of implementation of a direct communication channel with customers and absence of competitive strategies and prices.